Effects of the Enactive, Iconic, Symbolic (EIS) Intervention on Student Math Skills in Primary School - Marta Pellegrini; Valeria Di Martino; Roberto Trinchero (Journal of Educational, Cultural and Psychological Studies, 2025)
Abstract